Opportunity for Thailand's forgotten tigers: assessment of the Indochinese tiger Panthera tigris corbetti and its prey with camera-trap surveys. Issue 2 (27th March 2021) - Ash, Eric; Kaszta, Żaneta; Noochdumrong, Adisorn; Redford, Tim; Chanteap, Prawatsart; Hallam, Christopher; Jaroensuk, Booncherd; Raksat, Somsuan; Srinoppawan, Kanchit; Macdonald, David W.
Abstract: Dramatic population declines threaten the Endangered Indochinese tiger Panthera tigris corbetti with extinction. Thailand now plays a critical role in its conservation, as there are few known breeding populations in other range countries. Thailand's Dong Phayayen-Khao Yai Forest Complex is recognized as an important tiger recovery site, but it remains poorly studied. Here, we present results from the first camera-trap study focused on tigers and implemented across all protected areas in this landscape. Our goal was to assess tiger and prey populations across the five protected areas of this forest complex, reviewing discernible patterns in rates of detection. We conducted camera-trap surveys opportunistically during 2008–2017. We recorded 1, 726 detections of tigers in 79, 909 camera-trap nights. Among these were at least 16 adults and six cubs/juveniles from four breeding females. Detection rates of both tigers and potential prey species varied considerably between protected areas over the study period. Our findings suggest heterogeneity in tiger distribution across this relatively continuous landscape, potentially influenced by distribution of key prey species. This study indicates that the Dong Phayayen-Khao Yai Forest Complex is one of the few remaining breeding locations of the Indochinese tiger. Despite limitations posed by our study design, our findings have catalysed increased research and conservation interest in this globally important population at a critical time for tiger conservation in South-east Asia.